PENAMBAHAN NEUROMUSCULAR TRAINING PROGRAM DALAM MENINGKATKAN PERFORMA FUNGSIONAL ANKLE ATLET SEPAK BOLA LAKI-LAKI DENGAN RIWAYAT ANKLE SPRAIN - Pramono, Dominggus Ruku Yudit; Tinduh, Damayanti; Harlina, Harlina (Universitas Tribhuwana Tunggadewi, 2020)
When there is an ankle sprain injury the athlete has decreased functional ability and decreased instability of the ankle joint. One of the actions used to reduce the risk of injury and increase the performance of athletes is by providing a Neuromuscular Training Program (NMT). This study to prove the effect of the provision of the Neuromuscular Training Program on the functional performance. This study used a Randomized Pre Test and Post Test Group Design study design. Respondents of this study were male soccer athletes, amounting to 18 athletes who met the inclusion criteria, then divided into 2 groups randomly, each group consisted of 9 respondents. The study showed that there were differences in improvement in functional performance after the administration of the Neuromuscular Training Program in male soccer athletes with a history of ankle sprain. In the treatment group shows the results of functional performance (SLHT) with a value of p = 0,000 indicates a significant effect. Then the results of subjective functional performance measurements using Cumberland Ankle and Instability Tools (CAIT) in the treatment group showed the results of functional performance (CAIT) with a value of p = 0.005. From the results of the study that there were differences and improves in functional performance after the administration of the Neuromuscular Training Program in male soccer athletes with a history of ankle sprain.